What takes 'us' so long? The philosophical poverty of childhood studies and education. (August 2022) - Biswas, Tanu
My argument addresses a significant history of philosophical racism–a term borrowed from Mogobe Ramose. The argument is: philosophical racism makes the racist philosophically poor, too. I propose that two philosophical keystones, i.e., ontological simultaneity and mutual causation need to be further developed by engaging non-Western contributions. I conclude by emphasising that childhood studies could level the playing field by paying attention to the intersections of racism and adultism. In turn contribute to inseparable fields like the philosophy of education.